A randomised approach for enumerating migrated cells in a transwell migration assay - Kanesan, Livashini; Omar Zaki, Siti Sarah; Vidyadaran, Sharmili (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
The transwell migration assay is commonly used for assessing cell migration. It involves the enumeration of cells that have migrated across a pore-containing membrane. We describe a randomised approach to quantifying migrated cells and compare it to a conventional full cell count. We used ATP as a chemoattractant and automatic cell quantification performed on all fields (Full count; FC) or 10 randomly selected fields (Randomised count; RC). The two methods were compared by evaluating standard deviations (SD), coefficient of variation (CV) and using the Bland-Altman analysis. The dispersion of data is higher with the RC approach (3.77-6.66% CV for control; 3.89-4.48% CV for ATP-treated wells) compared to FC (0.27-0.46% CV for control; 0.05-0.09% CV for ATP-treated wells), but are acceptable considering that the number of migrated cells are in the thousands. Both methods verified that an ATP migration assay for BV2 microglia was established, demonstrating that the RC approach is reliable and comparable to a full count.